RELATIONSHIP OF CHRONIC MUSCULOSKETAL PAIN WITH METABOLIC SYNDROME IN THE DISCOURSE FIELD OF SCIENTIFIC KNOWLEDGE - Kalmykova, Yu. S.; Dzhym, M. O.; Dzhym, V. Yu. (Rehabilitation and Recreation, 2024)
The purpose of the article is to study the prevalence of chronic musculoskeletal pain in people with metabolic syndrome, as well as to study the problem and connection between metabolic syndrome and chronic pain. Material and methods: analysis of literary sources of scientometric databases PEDro, MEDLINE/ PubMed, Scopus, Web of Science, Google Scholar and generalization of scientific and methodological literature. Results. Today, one of the most difficult medical and social problems of modern society is metabolic syndrome. The incidence of metabolic syndrome in the population is high. Metabolic syndrome or “insulin resistance syndrome” is defined as a pathological condition characterized by the development of abdominal obesity, dyslipidemia, hypertension and carbohydrate metabolism disorders. Despite the fact that most countries have taken measures to promote healthy lifestyles, health problems remain serious and common among both older and younger populations. Chronic pain is one of the most common problems among individuals with metabolic syndrome. Chronic pain dramatically affects people in terms of their physical and psychological health, causing limited mobility, avoidance of activity, depression and anxiety, sleep disturbance and social isolation, all of which can in turn lead to significant disability in those with obesity. Chronic pain and obesity, common in people of all ages, can be barriers to health because they affect critical areas of quality of life such as physical functioning and mental health. Also, a sedentary lifestyle and hypokinesia are known risk factors for the development of obesity and chronic pain. Conclusions. A systematic analysis of the scientific literature on the research problem confirmed the relevance of developments related to restoring the quality of life of people with metabolic syndrome and chronic pain, since metabolic syndrome in combination with chronic pain is one of the most complex medical and social problems of modern society. Experts also note that people with metabolic syndrome associated with chronic pain face objective difficulties determined by the presence of serious health conditions, physical limitations and psychological problems. This problem is very urgent and requires further study.